The Reception of Paul the Apostle in the Works of Slavoj Žižek - Løland, Ole Jakob (Radical Theologies and Philosophies, 2018)
This is the first book devoted entirely to exploring Žižek's peculiar kind of Paulinism. It seeks to provide a full map of the Marxist philosopher's interpretations of Paul and critically engage with it. As one of several radical leftists of European critical thought, Žižek embraces the legacy of an ancient apostle in fascinating ways. This work considers Žižek's philosophical and political readings of Paul through the lens of reception history, and argues that through this recent philosophical turn to Paul, notions of the historical and philosophical are reproduced and negotiated anew.